THE SIMULATION AND DATA ANALYSIS OF TEMPERATURE SENSOR - Hilal Fauzi Ramadhan; Retno Dwi Kartika Sari; Adnan Prasetyo Alamsyah; Adrian Fadhillah; Rizki Nurhikmah; Sarah Aribah Miftahulfallah; Widya Rahma; Ari Firia; Dea Amelia Saputri; Irmansyah Irmansyah; Irzaman Irzaman (Spektra: Jurnal Fisika dan Aplikasinya, 2021)
The study have successfully simulated 40 units data of temperature sensor during heating process and cooling process. Simulated data in temperature sensor has interval time 3 to 18 seconds for 5 iterations that are combined with other 7 data temperature sensor until get 40 data iterations. The data which has been simulated and then plotted into a graph with the x-axis is time and y-axis is average heating process or cooling process. The graph formmed cupped-down with quadratic function for heating process and cupped-up for cooling process.